Metaheurísticas populacionais: estudo comparativo na sintonia de parâmetros de controladores clássicos - VIDAL, Juan Ferreira (Universidade Federal do Pará, 2017)
Population metaheuristics are techniques belonging to the field of Computational Intelligence and are based on natural models, have emerged as alternatives to solve optimization problems where the traditional techniques cannot be applied, or even where a solution model for the problem is not available with which the solution is found through empirical means. Given these capabilities to provide acceptable solutions in a timely manner for most of the complex problems encountered, metaheuristics has been applied successfully in most of the control system problems found in the literature. This work presents in general how the metaheuristics are being applied in the solution of control problems and performs a comparative study of performance among four algorithms bioinspirados in the tuning of the PID parameters. The following algorithms were used: Genetic Algorithm (AG), Genetic Algorithm in the Islands Model (AGMI), Bacterial Foraging Optimization (BFO) and Particle Swarm Optimization (PSO). The results demonstrate that the algorithms present an excellent performance in the tuning of the PID producing response that met the project requirements. Different systems with different characteristics were used to evaluate the algorithms. The PSO was shown as the best algorithm among the four used, producing response in a faster time and presented lower deviated standard in the trials.